Answer:
[tex](15s)^6[/tex] is the same as [tex]15^6[/tex] × [tex]s^6[/tex]
- The above statement can be proven by a rule related to exponents that states: [tex](ab)^c = a^c[/tex] × [tex]b^c[/tex]
[tex]3s^4[/tex] × [tex]5s^2[/tex] = [tex]15s^6[/tex]
- (Work for the equation above ---> You would multiply the 3 and 5 together (3 x 5 = 15) and then multiply the s terms together [tex]s^4[/tex] x [tex]s^2[/tex] , and this can be done using the exponent rule --> [tex]a^b[/tex] x [tex]a^c[/tex] = [tex]a^{b+c}[/tex]. This means that [tex]s^4[/tex] x [tex]s^2 = s^{4+2} = s^6[/tex]) This results in [tex]15s^6[/tex]
[tex]15s^6 \neq 15^6[/tex] x [tex]s^6[/tex]
Hope this helps in any way!! :D